Using the ODRL Profile for Access Control for Solid Pod Resource Governance - Pandit, Harshvardhan (My University, 2022)
This demo shows an ODRL editor where RDF policies can be defined and enforced to grant access to personal data stored in Solid Pods. Policies are represented using OAC, the ODRL profile for Access Control, which allows the definition of complex, fine-grained permissive and prohibitive policies that are aligned with GDPR requirements regarding the processing of personal data. In addition, a second demonstrator is presented to simulate an app’s request for data and examples of policies and consent record modelling are showcased.
Extended Semantic Web Conference (ESWC)
Extended Semantic Web Conference (ESWC)
Keywords: ODRL; Policy modelling; Solid; Access control; Access Control; SEMANTIC WEB